Sentence Repetition as a Tool for Screening Morphosyntactic Abilities of Bilectal Children with SLI - Theodorou, Elena; Kambanaros, Maria; Grohmann, Kleanthes K. (Frontiers in Psychology, 2017)
The clinical significance of sentence repetition tasks (SRT) for assessing children’s language ability is well recognized. Indeed, several screening and diagnostic instruments incorporate a sentence repetition subtest as part of the assessment battery. SRT has been identified as a good clinical marker for children with (specific) language impairment as it shows high diagnostic accuracy levels. Furthermore, qualitative analysis of repetition samples can provide information information to be used for intervention protocols. Despite the fact that SRT is a familiar task in assessment batteries across several languages, it has not yet been measured and validated in dialectal bilectal settings, such as Cypriot Greek, where the need for an accurate screening tool is urgent. . The aims of the current study are threefold. First, the performance of a group of (Cypriot) Greek-speaking children identified with SLI is evaluated using a SRT that elicits complex morphosyntactic structures. Second, the accuracy level of the sentence repetition task for the identification of SLI is explored. and the relationship of the task with other language tests used is examined. Third, a broad error analysis is carried out to examine and compare the morphosyntactic abilities of the participanting childrens. A total of 38 children aged 5 to 9 years participated in this study: a clinical group of children with SLI (n=16) and a chronological age-matched control group (n=22). The ability of the children to repeat complex morphosyntactic sentences structtures was assessed using a SRT consisting of 24 itemssentences. The results showed that the SRT yielded significant differences in terms of poorer performance of children with SLI compared to typically developing peers. The diagnostic accuracy of the task was was validated proved, since regression analysis showed that it the task is sensitive and specific enough to identify children with SLI. Moreover, there was a positive correlation of the SRT with various language tests. Finally, qualitative differences between the groups of children children with SLI and those with TLD regarding morphosyntactic abilities were detected. This study showed that a SRT that elicits morphosyntactically complex structures could be a potential clinical indicator for SLI in Cypriot Greek. The task has